The Potential of Cammelia sinensis (Tea Leaves) Active Compound as Alternative Therapy on castrate-resistant prostate cancer (CRPC) with Androgen Receptor Inhibition: In Silico Study - Mega Memory Rahasa Putra; Kurnia Penta Seputra (Biomolecular and Health Science Journal, 2022)
Introduction: Prostate cancer is a leading global cause of increased mortality and morbidity in men which can be complicated by castrate-resistant prostate cancer (CRPC). Pharmacological therapy by inhibiting the androgen receptor (AR) can inhibit prostate cancer progression. Tea leaves (Camellia sinensis) are believed to inhibit the prostate cancer progression but the mechanism is still unknown. Therefore, research on the mechanism by in silico study is needed with the AR as target protein.Methods: The effectivity of tea leaves’ active compound to inhibit androgen receptor was evaluated by docking server with abiraterone acetate as a control. The tea leaves' active compounds consist of catechin, epicatechin, epigallocatechin gallate, epigallocatechin, gallate epicatechin, gallocatechin gallate, and gallocatechinResults: The result showed that epicatechin, epigallocatechin, and gallocatechin have lower free binding energy (ΔG) and high amino acid residue similarity on AR compared with abiraterone acetate. But, it has lower surface interaction compared with abiraterone acetate. Conclusion: Epicatechin, epigallocatechin, and gallocatechin are predicted to have potential as alternative therapy in CRPC with AR Inhibition.